Borophene as an anode material for Zn-ion batteries: a first-principles investigation. (3rd May 2019) - Leng, Senlin; Sun, Xiaoya; Yang, Yingchang; Zhang, Renhui
Abstract: Generally, low intercalation voltage and diffusion energy barrier and high metallic conductivities are three key factors for anode materials. Borophene is analogue of graphene, which has been confirmed to be a right anode material for Ca, Mg, Na and Li ions batteries. In this work, we employ first-principles calculations to investigate the intercalation of Zn atom into the monolayer borophene sheet. We first identify the weaker binding sites as well the corresponding binding energies. Our calculations exhibit a weak binding energy of about 0.79 eV between the borophene substrate and Zn ions. Moreover, the binding energy decreases with increasing the Zn content. Besides, the advantages include small diffusion energy barriers and low average intercalation voltages are detected. Most remarkably, the storage capacity is as high as 433 mA h g −1 in the borophene sheet for Zn-ion batteries. Our results highly support that the borophene sheet can be an appealing anode material for Zn-ion batteries with high power density.